Femtosecond Laser Fabrication of Wettability-Functional Surfaces: A Review of Materials, Structures, Processing, and Applications - Zelin Chen; Jiantao Zhou; Wenyang Cen; Yinzhou Yan; Wei Guo (Nanomaterials)
Wettability-functional surfaces are crucial in both theoretical investigation and engineering applications. Compared to traditional micro/nano fabrication methods (such as ion etching, sol–gel, chemical vapor deposition, template techniques, and self-assembly), femtosecond laser processing has unique advantages, such as unmatched precision, flexible controllability, and material adaptability, widely used for the fabrication of wettability-functional surfaces. This paper systematically discusses the principle and advancement of femtosecond laser micro/nano processing in regulating surface wettability and analyzes the laser modulation mechanisms and structural design strategies for wettability-functional surfaces on various materials. Additionally, this paper reviews the practical applications of femtosecond laser-based wettability-functional surfaces in environmental engineering, aerospace, and biomedical fields, while highlighting the challenges and future directions for femtosecond laser processing of wettability-functional surfaces.